Atomistic Observation of the Local Phase Transition in MoTe2 for Application in Homojunction Photodetectors. Issue 19 (11th April 2022) - Wang, Yalan; Zhang, Miao; Xue, Zhongying; Chen, Xinqian; Mei, Yongfeng; Chu, Paul K.; Tian, Ziao; Wu, Xing; Di, Zengfeng
Abstract: Direct atomic‐scale observation of the local phase transition in transition metal dichalcogenides (TMDCs) is critically required to carry out in‐depth studies of their atomic structures and electronic features. However, the structural aspects including crystal symmetries tend to be unclear and unintuitive in real‐time monitoring of the phase transition process. Herein, by using in situ transmission electron microscopy, information about the phase transition mechanism of MoTe2 from hexagonal structure (2H phase) to monoclinic structure (1T′ phase) driven by sublimation of Te atoms after a spike annealing is obtained directly. Furthermore, with the control of Te atom sublimation by modulating the hexagonal boron nitride (h‐BN) coverage in the desired area, the lateral 1T′‐enriched MoTe2 /2H MoTe2 homojunction can be one‐step constructed via an annealing treatment. Owing to the gradient bandgap provided by 1T′‐enriched MoTe2 and 2H MoTe2, the photodetector composed of the 1T′‐enriched MoTe2 /2H MoTe2 homojunction shows fast photoresponse and ten times larger photocurrents than that consisting of a pure 2H MoTe2 channel. The study reveals a route to improve the performance of optoelectronic and electronic devices based on TMDCs with both semiconducting and semimetallic phases. Abstract : The atomic structure changes from 2H MoTe2 to 1T′ MoTe2 are monitored directly by in situ transmission electron microscopy observation and the seamless interface can be formed between these two phases. By patterning hexagonal boron nitride on MoTe2, a lateral 1T′‐enriched MoTe2 /2H MoTe2 homojunction photodetector can be built, which exhibits fast photo response due to the gradient bandgap alignment.